Digital platform for managing investment projects within the "government-business-society" relations based on partnership - Petrova, I. (Економічний вісник Донбасу, 2024)
The article explores the role of digital platforms in managing investment projects within the interaction framework of "government-business-society" based on partnership principles. It is substantiated that digital platforms serve as a key tool for enhancing the efficiency of public-private partnership (PPP) project management by facilitating centralized communication, information exchange, and optimization of decision-making processes. The main functional capabilities of digital platforms are analyzed, particularly their role in increasing transparency, reducing transaction and organizational costs, automating partner selection processes, conducting tenders, and monitoring contract execution. Ukrainian digital transformation initiatives in the PPP sector are examined, including the DREAM platform (Digital Restoration Ecosystem for Accountable Management) and the pilot project for implementing a Unified Digital Integrated Information-Analytical System for managing the reconstruction process of facilities. Legislative initiatives aimed at improving the mechanism for attracting private investments through PPPs are highlighted, which include the creation of an electronic procurement system for PPP projects in accordance with European Union standards. It is proven that digital platforms can contribute to attracting international investors and ensuring the long-term sustainability of PPP projects. The necessity of developing a comprehensive digital ecosystem that covers all stages of the PPP lifecycle and integrates with existing state information systems is justified. The conclusion is drawn on the strategic necessity of implementing a full-fledged digital platform for PPP project management to enhance efficiency, transparency, and openness in interactions between the public, private, and civil sectors. У статті досліджується роль цифрових платформ в управлінні інвестиційними проєктами в рамках взаємодії "влада-бізнес-суспільство" на засадах партнерства. Обґрунтовано, що цифрові платформи є ключовим інструментом підвищення ефективності управління проєктами публічно-приватного партнерства (ППП) завдяки централізованій комунікації, обміну інформацією та оптимізації процесів прийняття рішень. Проаналізовано основні функціональні можливості цифрових платформ, зокрема їхню роль у підвищенні прозорості, зниженні трансакційних і організаційних витрат, автоматизації процесів вибору партнерів, проведення тендерів та моніторингу виконання угод. Розглянуто українські ініціативи цифрової трансформації у сфері ППП, включаючи платформу DREAM (Digital Restoration Ecosystem for Accountable Management) та експериментальний проєкт із впровадження Єдиної цифрової інтегрованої інформаційно-аналітичної системи управління процесом відбудови об'єктів. Виокремлено законодавчі ініціативи щодо вдосконалення механізму залучення приватних інвестицій через публічно-приватне партнерство, які передбачають створення електронної системи закупівель для проєктів ППП відповідно до стандартів Європейського Союзу. Доведено, що цифрові платформи можуть сприяти залученню міжнародних інвесторів та забезпеченню довгострокової стійкості проєктів ППП. Обґрунтовано необхідність створення комплексної цифрової екосистеми, що охоплюватиме всі етапи життєвого циклу ППП та забезпечуватиме інтеграцію з існуючими державними інформаційними системами. Зроблено висновок про стратегічну необхідність впровадження повноцінної цифрової платформи управління проєктами ППП для підвищення ефективності, прозорості та відкритості взаємодії між публічним, приватним і громадським секторами.